Avaliação dos polimorfismos CCR5 32 e CCR5 59029 A/G na toxoplasmose ocular - Faria Junior, Geraldo Magela de (2018)
C-C chemokine receptor type 5 (CCR5) is a chemokine receptor that influences the immune response to infectious and parasitic diseases. Objective: This study aimed to determine whether the CCR5Δ32 and CCR5 59029 A/G polymorphisms are associated with the development of ocular toxoplasmosis in humans. Methods: Patients with positive serology for Toxoplasma gondii were analyzed and grouped as "with ocular toxoplasmosis" (G1: n = 160) or "without ocular toxoplasmosis" (G2: n = 160). A control group (G3) consisted of 160 individuals with negative serology. The characterization of the CCR5Δ32 and CCR5 59029 A/G polymorphisms was by PCR and by PCRRFLP, respectively. For the statistical analysis, chi-square and Fisher's exact test were performed for comparisons and multivariate logistic regression. Results: The difference between groups in respect to the mean age was statistically significant (G1 vs.G2: p-value <0.0001; t = 7.21; DF = 318; G1 vs.G3: p-value <0.0001; t = 4.32; DF = 318; G2 vs. G3: p-value <0.0001; t = 9.62; DF = 318). The Nagelkerke r² value was 0.040. There were statistically significant differences for the CCR5/CCR5 (p-value = 0.008; OR = 0.261), AA (p-value = 0.007; OR = 2.974) and AG genotypes (p-value = 0.018; OR = 2.447) between G1 and G2. Conclusion: Individuals with the CCR5/CCR5 genotype and simultaneously with the CCR5- 59029 AA or AG genotypes have a greater risk of developing ocular toxoplasmosis (4% greater), which may be associated with a strong and persistent inflammatory response in ocular tissue.